Kajian Perencanaan Pemanfaatan Transportasi Laut Dan Sungai Untuk Mengatasi Kemacetan Di Kota Makassar - Faisal, Agung; Nurdin, Abd Rahim; Yunus, Ahmad Yauri (Program Studi Teknik Sipil Universitas Bosowa, 2025)
Makassar City is experiencing the same struggle with other big cities, namely the problem of urban transportation. The level of vehicle movement in Makassar City is quite high as a result, causing congestion in the downtown area and in the suburbs. Water transportation media cannot be separated from the origin of the transportation system above, namely the activity in the river circulation area so that it has the potential to be developed, this study analyzes the river route as a water transportation network into Makassar City transportation. Increasing the use of water transportation routes to generate social activities and a form of transportation system used for the transportation of goods and passengers through water. The advantages of river or canal transportation means that it is cheap, easy, relatively safe, the carrying capacity can be high in sync using the culture of its use, simple technology. The main weakness comes from river transportation, which means slow movement and many areas that are not traversed by commercial shipping channels.